2020
DOI: 10.1039/c9sc05892c
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic transformation of lignin with guaiacol as the only liquid product

Abstract: La(OTf)3 can catalyze the transformation of lignin efficiently with guaiacol as the only liquid product, and guaiacol produced can be isolated easily in a scaled up experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 48 publications
0
43
0
1
Order By: Relevance
“…These works achieved an impressive yield of bio‐based phenols from raw biomass via (i) RCF combined with demethoxylation/dealkylation; and (ii) oxidative depolymerization followed by decarboxylation. La(OTf) 3 could catalyze the depolymerization of lignin to obtain alkyl‐guaiacol and alkyl‐syringol, which underwent further dealkylation and demethoxylation to obtain an appreciable yield (25.5 wt %) of guaiacol (Figure d) . Ferulic acid could be derived from ferulate structure in herbaceous biomass, and Brønsted acid catalyzed defunctionalization of ferulic acid to bio‐catechol was reported, which unlocked the potential to produce catechol from raw biomass .…”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…These works achieved an impressive yield of bio‐based phenols from raw biomass via (i) RCF combined with demethoxylation/dealkylation; and (ii) oxidative depolymerization followed by decarboxylation. La(OTf) 3 could catalyze the depolymerization of lignin to obtain alkyl‐guaiacol and alkyl‐syringol, which underwent further dealkylation and demethoxylation to obtain an appreciable yield (25.5 wt %) of guaiacol (Figure d) . Ferulic acid could be derived from ferulate structure in herbaceous biomass, and Brønsted acid catalyzed defunctionalization of ferulic acid to bio‐catechol was reported, which unlocked the potential to produce catechol from raw biomass .…”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…The low yield of guaiacol hindered its further industrial application owing to the complicated and costly purification process. More recently, our group reported a novel route to produce pure guaiacol selectively from lignin using La(OTf) 3 as a Lewis acid catalyst in methanol/water solvent and the yield of guaiacol reached up to 25.5 wt %. This is the first work on the transformation of lignin with guaiacol as the only liquid product.…”
Section: Directed Cleavage Of Ether Linkages In the Side Chain Of Ligninmentioning
confidence: 99%
“…Rather than gasifying lignin, a next best alternative technology within the context of more conventional heterotrophic fermentation would be a process that converts lignin to guaiacol, thereafter converting the guaiacol to BDO via the 3-oxoadipate pathway. Shen et al (2020) demonstrated that lignin can be selectively converted to guaiacol as an alternate technology to gasification. C. necator is capable of degrading .…”
Section: Systems Biology For Bdo Synthesis Using Co 2 and H 2 And Guaiacol As Sole Energy And Carbon Sourcesmentioning
confidence: 99%